2022
DOI: 10.3389/fendo.2022.1023867
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between triglyceride–glucose index and carotid plaques in a high-stroke-risk population in southeast china: A population-based cross-sectional survey

Abstract: BackgroundCervical arterial atherosclerosis (CAA) is an important risk factor of stroke in China. The triglyceride–glucose (TyG) index is a simple and low-cost marker for ischemic stroke. Whether the TyG index predicts cervical arterial atherosclerosis remains uncertain. This study aimed to investigate the relationship between the TyG index and cervical arterial atherosclerosis.MethodsThis cross-sectional study was conducted in residents aged ≥40 years in the general population of southeast China. All particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Subjects with at least three of these risk factors were classified into the high-risk stroke population, while the participants with less than 3 risk factors but having one of the following medical histories: diabetes, hypertension, and atrial fibrillation were defined as medium-risk group. Low risk of stroke was defined as having < 3 risk factors and without diabetes, hypertension, and atrial fibrillation [ 30 ]. The atherogenic index of plasma (AIP) was defined as the logarithm to the base 10 of the ratio of fasting plasma triglyceride (TG) (mg/dL) to high-density lipoprotein cholesterol (HDL-C) [log (TG/HDL-C)] [ 20 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with at least three of these risk factors were classified into the high-risk stroke population, while the participants with less than 3 risk factors but having one of the following medical histories: diabetes, hypertension, and atrial fibrillation were defined as medium-risk group. Low risk of stroke was defined as having < 3 risk factors and without diabetes, hypertension, and atrial fibrillation [ 30 ]. The atherogenic index of plasma (AIP) was defined as the logarithm to the base 10 of the ratio of fasting plasma triglyceride (TG) (mg/dL) to high-density lipoprotein cholesterol (HDL-C) [log (TG/HDL-C)] [ 20 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, one of our previous studies has found that the TyG index is an independent predictor of carotid plaque formation in people over 40 years of age at high risk of stroke [18]. TyG index is closely related to stroke, particularly LAA.…”
Section: Introductionmentioning
confidence: 81%